2005
DOI: 10.1682/jrrd.2005.02.0045
|View full text |Cite
|
Sign up to set email alerts
|

Chronicity of pain associated with spinal cord injury: A longitudinal analysis

Abstract: This study determined the stability of self-reported clinical pain characteristics and pain-induced interference with sleep and daily activities in people with spinal cord injury. The study followed up a previous survey that identified clinical pain patterns (i.e., neuropathic pain below the level of injury; upper-limb pain in tetraplegia; and severe, persistent pain). A confirmatory factor analysis (CFA) of the present study's data confirmed the previously observed pain patterns. The CFA also confirmed positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
83
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 49 publications
2
83
1
Order By: Relevance
“…The finding that MD pains are intense and constant, interfere with daily living, and are aggravated by many factors adds to the body of literature that suggests that current treatments for pain in the SCI population are mostly insufficient [8,[16][17][18][19][20][21]. Pains that are severe, exacerbated by various stimuli encountered on a daily basis, and constantly present are bound to significantly interfere with activities of life beyond the functional limitations imposed by the SCI itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that MD pains are intense and constant, interfere with daily living, and are aggravated by many factors adds to the body of literature that suggests that current treatments for pain in the SCI population are mostly insufficient [8,[16][17][18][19][20][21]. Pains that are severe, exacerbated by various stimuli encountered on a daily basis, and constantly present are bound to significantly interfere with activities of life beyond the functional limitations imposed by the SCI itself.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of chronic pain has been reported to decrease quality of life after SCI [2,[10][11][12] and to frequently interfere with both sleep and common daily activities [2,[5][6]8,13]. Chronic pain in individuals with SCI is particularly problematic because several types of pain may exist simultaneously [2,[6][7][8][9][14][15], and many of these pains are refractory to currently available treatments [8,[16][17][18][19][20][21]. Because pain in this patient population is heterogeneous and persons with SCI often present with more than one type of pain, each pain should be evaluated separately to the extent possible.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of persons complaining of chronic pain report pain onset within the first 6 months of their injury, irrespective of the type of pain. 5,10,[14][15][16] Some studies have reported more delayed pain onset with visceral pain. 5,16 Preliminary longitudinal studies have shown relatively stable pain patterns over time in persons with chronic SCI, with few individuals reporting dramatic changes in pain location, type or intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies estimate that the prevalence of chronic pain after SCI is more than 75 percent [1][2][3]. Persons with SCI consistently report average pain levels between 4 and 6 in studies using the 0-10 numerical rating scale (NRS) [4][5], pain levels that are high enough to warrant comprehensive treatment and prompt follow-up in primary-care settings [6]. Pain is severe, with a strong negative impact on daily functioning, in about one-third of persons with SCI [1][2].…”
Section: Introductionmentioning
confidence: 99%
“…Pain is severe, with a strong negative impact on daily functioning, in about one-third of persons with SCI [1][2]. Of significant concern is the finding that once pain conditions following SCI emerge, they tend to persist [3][4] or worsen [2,7] over time, despite the many efforts to treat this pain. In summary, while pain is a ubiquitous, recalcitrant problem among persons with SCI, the degree to which pain has a pronounced effect on functioning is much more variable.…”
Section: Introductionmentioning
confidence: 99%